Counterculture and Social Revolution in the Context of Project Activity. Appropriate Technology and the Whole Earth Catalog - Sazikov Aleksey V. (Художественная культура)
The article examines the importance of counterculture and alternative technologies, primarily appropriate technologies, in shaping the environmental movement aimed at using scientific achievements, new technologies, ecological thinking, and ecodesign in the social revolution in the West in the 1960s and 1970s. Maintaining energy and information awareness were described as the basic skills needed to change the system. The article shows how under the influence of the politics of the New Left the representatives of the counterculture, such as the publisher of the Whole Earth Catalog Stuart Brand, designers Richard Buckminster Fuller and Victor Papanek, and organizations such as the New Alchemy Institute began to work on creating an alternative society from scratch, adapting science and technology for people. The fusion of technology and counterculture became the key to personal freedom and self-sufficiency.